Diagnóstico y propuestas comunitarias para el mejoramiento integral del barrio, El Faro, comuna 8. Medellín (2014)
This text presents: on the one hand, the results of an investigative exercise, which makes visible the deepest problems of the inhabitants of the communities swallows and the lighthouse of 8 commune of the city of Medellin, an exercise that be stepped forward in response to the process of institutional intervention arising from the constant processes of transformation of the city, which have led to displacement and rests with the same realities of those communities; on the other hand, it presents the proposal of solution built from the same communities face these problems.